A variety of exact solutions for the time fractional Cahn-Allen equation - Guner, Ozkan; Bekir, Ahmet; Cevikel, Adem C. (SPRINGER HEIDELBERG, 2015)
In this paper, the nonlinear time fractional Cahn-Allen equation is studied by three distinct methods. These methods are also applied to derive a variety of travelling wave solutions with distinct physical structures for this nonlinear fractional equation. As a result, different types of exact solutions are obtained. The three methods demonstrate power, reliability and efficiency.
Keywords: EXP-FUNCTION METHOD; PARTIAL-DIFFERENTIAL-EQUATIONS; NONLINEAR EVOLUTION-EQUATIONS; 1ST INTEGRAL METHOD; (G'/G)-EXPANSION METHOD; MATHEMATICAL PHYSICS; COMPLEX TRANSFORM; WAVE SOLUTIONS; CALCULUS; Physics